Dissecting the molecular architecture of integrin adhesion sites by cryo-electron tomography - Patla, Israel; Volberg, Tova; Elad, Nadav; Hirschfeld-Warneken, Vera; Grashoff, Carsten; Fässler, Reinhard; Spatz, Joachim P.; Geiger, Benjamin; Medalia, Ohad (Nature cell biology, 2010)
Little is known about the ultrastructure of focal adhesions, compared with their extensive molecular characterization. Cryo-electron tomography provides novel insights into the internal sub-structures at the interface between adhesions and the actin cytoskeleton.